2022
DOI: 10.1097/01.aog.0000825816.61927.41
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Menopausal Hormone Therapy Acceptance [A134]

Abstract: INTRODUCTION:There is a paucity of data on race and ethnicity in hormone therapy (HT) acceptance in previous menopause treatment studies. Our primary objective was to examine differences in HT acceptance between self-reported race and ethnic groups. Our secondary objective was to assess patient comorbidities and trends in reported symptom frequency at presentation in a menopause-focused care clinic.METHODS:Retrospective medical record review of patients presenting to a single menopause clinic from July 2018 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The prior literature has also demonstrated that White women are more likely to be prescribed HRT in comparison to Black women [ 28 ]. These data are supported within the demographics of our study, listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The prior literature has also demonstrated that White women are more likely to be prescribed HRT in comparison to Black women [ 28 ]. These data are supported within the demographics of our study, listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%